Analysis Of The Placement Pattern And The Needs Of The Rain Station With Kagan-Rodda Methode On Das Progo Yogyakarta - Jantiara Eka Nandiasa; Masnia Masnia; Mamiek Purwaning (NAROTAMA UNIVERSITY, Indonesia, 2021)
Climate change that occurs has an impact on various fields. In the Yogyakarta region, most of the people work in agriculture and fishing. Where the two fields are closely related to rainfall data and rainfall patterns. Based on these conditions, it is necessary to conduct a study on the need for maximum rainfall data. From the data obtained from the Serayu Opak River Basin Center for the Progo Watershed in Yogyakarta, there are 8 active rain stations that are still operating, but they are not maximized because they are often damaged. So that it is necessary to analyze the needs of the rain station and the placement pattern needed to obtain the maximum rainfall data. The method used in this research is the Kagan-Rodda method. This method can analyze the needs and distribution patterns of the rain stations required by calculating the rainfall data from existing stations. From the calculation with this method, it is obtained that the need for rain stations for the Progo River Basin Yogyakarta region is 11 stations. It is recommended to add 3 new stations with a distribution pattern as described with the distance between stations of 12,742 km.